Human and animal evidence of potential transgenerational inheritance of health effects: An evidence map and state-of-the-science evaluation. (June 2018) - Walker, Vickie R.; Boyles, Abee L.; Pelch, Katherine E.; Holmgren, Stephanie D.; Shapiro, Andrew J.; Blystone, Chad R.; Devito, Michael J.; Newbold, Retha R.; Blain, Robyn; Hartman, Pamela; Thayer, Kristina A.; Rooney, Andrew A.
Abstract: Background: An increasing number of reports suggest early life exposures result in adverse effects in offspring who were never directly exposed; this phenomenon is termed "transgenerational inheritance." Given concern for public health implications for potential effects of exposures transmitted to subsequent generations, it is critical to determine how widespread and robust this phenomenon is and to identify the range of exposures and possible outcomes. Objectives: This scoping report examines the evidence for transgenerational inheritance associated with exposure to a wide range of stressors in humans and animals to identify areas of consistency, uncertainty, data gaps, and to evaluate general risk of bias issues for the transgenerational study design. Methods: A protocol was developed to collect and categorize the literature into a systematic evidence map for transgenerational inheritance by health effects, exposures, and evidence streams following the Office of Health Assessment and Translation (OHAT) approach for conducting literature-based health assessments. Results: A PubMed search yielded 63, 758 unique records from which 257 relevant studies were identified and categorized into a systematic evidence map by evidence streams (46 human and 211 animal), broad health effect categories, and exposures. Data extracted from the individual studies are available in the Health Assessment Workspace Collaborative (HAWC) program. There are relatively few bodies of evidence where multiple studies evaluated the same exposure and the same or similar outcomes. Studies evaluated for risk of bias generally had multiple issues in design or conduct. Conclusions: The evidence mapping illustrated that risk of bias, few studies, and heterogeneity in exposures and endpoints examined present serious limitations to available bodies of evidence for assessing transgenerational effects. Targeted research is suggested to addressed inconsistencies and risk of bias issues identified, and thereby establish more robust bodies of evidence to critically assess transgenerational effects - particularly by adding data on exposure-outcome pairs where there is some evidence (i.e., reproductive, metabolic, and neurological effects). Highlights: Transgenerational effects are reported in both humans and animals. There are few bodies of evidence evaluating the same exposure and similar outcomes. Risk of bias assessment identified issues in study design, conduct, and reporting. Heterogeneity, bias limit bodies of evidence assessing transgenerational effects. Target future data to address inconsistencies and risk of bias issues.